Getting it - Sanchez, Alex, 1957- (Simon Pulse, 2006)
"Hoping to impress a sexy female classmate, fifteen-year-old Carlos secretly hires gay student Sal to give him an image makeover, in exchange for Carlos's help in forming a Gay-Straight Alliance at their Texas high school."
Keywords: literatura pro mládež; gayové; juvenile literature; gay men; americké romány; American fiction